Species of Strigea (Digenea: Strigeidae), parasites of the savanna hawk Buteogallus meridionalis (Aves: Accipitridae) from Argentina, with the description of a new species - Lunaschi, Lía I; Drago, Fabiana B (Folia parasitologica, 2009)
A new strigeid digenean, Strigea meridionalis sp. n., is described from the small intestine of the savanna hawk, Buteogallus meridionalis (Latham) (Aves: Accipitridae), from Formosa Province, Argentina. This species is characterised by the absence of a neck region in the hindbody, the presence of entire testes, a copulatory bursa with a membranous fold originated from the muscular ring (Ringnapf) and by the arrangement of vitelline follicles in the forebody. Other two strigeid species collected from the savanna hawk, Strigea elliptica (Brandes, 1888) and Strigea microbursa Pearson et Dubois, 1985, are described and illustrated. Strigea microbursa is reported for the first time from the Neotropical Region and B. meridionalis represents a new host record for S. elliptica. These findings allow us to increase the knowledge of these species, adding new metric and morphological data. A key to the species of the Neotropical Strigea Abildgaard, 1790 is presented including data on their geographical distribution.
Keywords: Trematoda; Hawks; Bird Diseases; Intestines; některé rody čeledi Accipitridae; Animals; Financing, Organized; nemoci ptáků; financování organizované; Argentina; zvířata; střeva